Colon stenting in benign diverticular stricture - a case report and review of literature - Hany Eskarous; Mahesh Krishnamurthy; Endeshaw Habtesilassie (Greater Baltimore Medical Center, 2021)
Background: Colonic stricture is a feared complication with varied etiology ranging from malignant obstruction to benign diseases. One such condition is recurrent diverticulitis-related strictures. Objectives & Methods: We report a case of a 48-year-old male patient with stricture of the sigmoid colon. The patient refused Sigmoid colon resection. He underwent stent placement and Two weeks later presented with constipation and abdominal discomfort. On Computed Tomography (CT) we discovered stent migration and consequent large bowel obstruction. Patient agreed on undergoing sigmoidectomy with a colostomy. Conclusion: Indication of SEMS for benign lesions remains unclear. Based on the current data, in benign colorectal obstructive lesions, SEMS is a viable option as a bridge to surgery when no other alternative option is available. However, the ASCRS 2020 guidelines did not point to SEMS as an option given the high rate of complications. Our patient was treated with a stent because he refused the resection surgery and found relief for a certain period before developing stent migration. Hence, the patients should be educated about the short and long-term potential effects of stenting before performing the procedure in benign strictures.